2017
DOI: 10.2135/cropsci2016.05.0408
|View full text |Cite
|
Sign up to set email alerts
|

Gains in Maize Genetic Improvement in Eastern and Southern Africa: II. CIMMYT Open‐Pollinated Variety Breeding Pipeline

Abstract: Open‐pollinated varieties (OPVs) still represent a significant proportion of the maize (Zea mays L.) seed system in many countries of sub‐Saharan Africa. The International Maize and Wheat Improvement Centre (CIMMYT) has been breeding improved maize varieties for the stress‐prone environments experienced by most smallholder farmers in eastern and southern Africa for over 30 yr. Hybrid breeding is now the major focus of the CIMMYT breeding pipeline. However, OPVs are generated within the hybrid pipeline. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 27 publications
5
69
3
1
Order By: Relevance
“…For tropical open-pollinated maize varieties, realized genetic gains reached 0.109 ton ha −1  yr −1 in the early maturity group, and 0.079 ton ha −1  yr −1 in the intermediate-to-late group (Masuka et al 2017b). Therefore, the genetic gains from the RCGS observed in the MPPs used in this study (0.100 ton ha −1  yr −1 ) are at the same or higher level than those observed in other studies under phenotypic selection but with a shorter breeding cycle.…”
Section: Discussionmentioning
confidence: 99%
“…For tropical open-pollinated maize varieties, realized genetic gains reached 0.109 ton ha −1  yr −1 in the early maturity group, and 0.079 ton ha −1  yr −1 in the intermediate-to-late group (Masuka et al 2017b). Therefore, the genetic gains from the RCGS observed in the MPPs used in this study (0.100 ton ha −1  yr −1 ) are at the same or higher level than those observed in other studies under phenotypic selection but with a shorter breeding cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Using this simultaneous selection approach, Bänziger et al (2006) developed hybrids that have shown a consistent yield advantage over private seed company hybrid checks for all testing environments. Masuka et al (2017aMasuka et al ( , 2017b evaluated genetic gains in the CIMMYT ESA maize hybrid and OPV breeding programs during the period 2000 to 2010. Hybrid gains in grain yield under optimal, managed drought, random drought, low N, and maize streak virus infested conditions were estimated at 1.4, 0.85, 0.85, 0.62, and 2.2% per season, respectively.…”
Section: Core Ideasmentioning
confidence: 99%
“…Much higher yield gains of 1.7% yr −1 were reported by Tollenaar (1989) for outstanding maize hybrids developed between the late 1950s and late 1980s and evaluated under drought conditions in Canada. For example, Masuka et al (2017b) demonstrated annual gains in grain yield of 0.029, 0.085, 0.11, and 0.193 Mg ha −1 for early-maturing open-pollinated varieties (OPVs) under natural drought, low N, optimal conditions, and infestation of the Maize streak virus (MSV), respectively, in Eastern and Southern Africa (ESA). For example, Masuka et al (2017b) demonstrated annual gains in grain yield of 0.029, 0.085, 0.11, and 0.193 Mg ha −1 for early-maturing open-pollinated varieties (OPVs) under natural drought, low N, optimal conditions, and infestation of the Maize streak virus (MSV), respectively, in Eastern and Southern Africa (ESA).…”
mentioning
confidence: 99%
“…However, only a few reports are available on yield gains for tropical maize evaluated under drought stress. Genetic gains under random drought, low-N, rainfed, and MSV-infested conditions for the intermediate-late-maturing cultivars were reported to be 0.042, 0.053, 0.079, and 0.109 Mg ha −1 yr −1 , respectively (Masuka et al, 2017b). Genetic gains under random drought, low-N, rainfed, and MSV-infested conditions for the intermediate-late-maturing cultivars were reported to be 0.042, 0.053, 0.079, and 0.109 Mg ha −1 yr −1 , respectively (Masuka et al, 2017b).…”
mentioning
confidence: 99%